PEMBERIAN ASI BERHUBUNGAN DENGAN DERAJAT STUNTING BAYI USIA 6-12 BULAN - Diyah Arini; Christina Yuliastuti; Essa Nevya Putri (POLTEKKES KEMENKES MANADO, 2020)
Background: Mother's Milk (ASI) is the most important food and drink for babies. Additional food besides breast milk at an earlier age can increase morbidity. The degree of stunting is defined as a measure of nutritional status based on height by age in the z-score that is categorized into mild stunting, moderate stunting and severe stunting. Objective: To analyze the relationship between breastfeeding and the degree of stunting in infants aged 6-12 months in the Work Area of ​​the Kenjeran Health Center in Surabaya. Method: In this study using a correlation analytic research design with a cross sectional approach. The research population of all stunting infants in the working area of ​​the Surabaya Kenjeran Health Center was 325 infants in 4 Kelurahan including Kenjeran Kelurahan, Bulak Kelurahan, Kedung Cowek Kelurahan, and Sukolilo Kelurahan. The sample technique uses Probability Sampling by using Stratified Random Sampling as many as 97 babies. The research instrument used a questionnaire to determine breastfeeding. As well as measuring the degree of stunting using an observation sheet adjusted to the z-score table (body length / age). Results: The results showed that infants aged 6-12 months who experienced the worst degree of stunting consume milk partially. The Spearman rho test showed an association between breastfeeding and the degree of stunting ρ = 0,000 (ρ <α = 0.05). Conclusion: Breastfeeding is related to the degree of stunting, so that it can be socialized about the movement of the first 1000 days of life and counseling about providing complementary foods suitable for the age of the baby to cadres in the Work Area of ​​the Kenjeran Health Center in Surabaya.